Black Misandry and the Killing of Black Boys and Men. Issue 2 (2nd April 2020) - Brooms, Derrick R.; Clark, Jelisa S.
ABSTRACT: The ways in which Black boys and men are framed and projected within U.S. society reveal clear messages of Black misandry, Negrophobia, and scripting of Black male bodies. From "tar baby" to "thug" Black boys and men are always already under surveillance—leading to prejudice, physical violence, and criminalized projections. Yet, commitments to and investments in colorblind rhetoric and ideology seem to obscure the realities that gendered racism against Black men and boys are not newsworthy and have little, if anything, to do with race. In fact, as has been seen in response to some of the more high-profile cases in the public killing of Black men and boys, colorblind rhetoric has been used to deny the racial realities of these events and experiences. To contribute to this literature, the current study analyzes qualitative interview data from 25 individuals focused on their perceptions of race and the killing of Black boys and men. Our data offer two critical points to contemporary discussions of race and gendered racism. First, the already available scripts about Black male bodies (e.g., fear and avoidance) can be used to justify racism and violence against Black boys and men. And, second, racism can be rationalized based on people's preconceived notions and, even more specifically, because of their color consciousness (e.g., Black male equals threat). The findings reveal that the stereotyping and profiling of Black boys and men are rationalized within a national rhetoric that posits Black boys and men as problems and their killings are justified by Black misandry, which ultimately reveals the costs of their Blackmaleness.